METHODOLOGICAL AND EMPIRICALLY PRINCIPLES OF ASSESSING THE LEVEL OF BALANCED RURAL DEVELOPMENT OF UKRAINE - Сава, А. П.; Ільїн, В. Ю.; Роздимаха, С. М. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
The aim of the study is to substantiate the methodological tools for the integral assessment of rural development in terms of economic, social and environmental components and to determine the level of development of rural areas. For this purpose, the author has analyzed the existing methodological approaches to the study of socioeconomic processes in rural areas; grounded scientific methods and formed a system of criteria, indicators and indicators for assessing rural development. Assessment of the state of rural areas structurally involves the analysis of its organizational formation, the development of entrepreneurship as an economic basis, social infrastructure facilities, rational use of natural resources. A comprehensive assessment of the state and rural development has been carried out, it will ensure the identification and delivery of a stable relationship between the rates of economic growth, the level of development of society and the proper state of environmental management. On the basis of this, an effective mechanism for the implementation of management decisions to achieve the specified development parameters is proposed.